THE IMPORTANCE AND ADVANTAGES OF LEARNING FOREIGN LANGUAGES IN MODERN SOCIETY - Ilxomova Dilshoda Jasur qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: In modern society, learning foreign languages has become increasingly important. With globalization connecting countries through business, education, technology, and travel, knowing more than one language is a valuable skill. It helps people communicate with others from different cultures and backgrounds, making the world more connected and cooperative.One of the main advantages of learning foreign languages is better communication. People who speak multiple languages can travel more easily, make international friends, and work with people from other countries. It also improves job opportunities, as many companies prefer employees who can communicate with foreign partners and customers.Learning foreign languages also develops cognitive skills. It improves memory, concentration, and problem-solving abilities. Students who learn new languages often become more creative and flexible thinkers. In addition, language learning helps people understand other cultures, traditions, and ways of thinking, which increases tolerance and respect among different nations.In conclusion, learning foreign languages plays an essential role in modern society. It opens doors to new opportunities, strengthens communication, improves mental abilities, and promotes cultural understanding. Therefore, studying foreign languages is a useful and valuable investment for personal and professional growth.